2006
DOI: 10.1002/fld.1366
|View full text |Cite
|
Sign up to set email alerts
|

A high‐order accurate method for two‐dimensional incompressible viscous flows

Abstract: SUMMARYA high-order accurate solution method for complex geometries is developed for two-dimensional flows using the stream function-vorticity formulation. High-order accurate spectrally optimized compact schemes along with appropriate boundary schemes are used for spatial discretization while a two-level backward Euler implicit scheme is used for the time integration. The linear system of equations for stream function and vorticity are solved by an inner iteration while contravariant velocities constitute out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 30 publications
(21 reference statements)
1
5
0
Order By: Relevance
“…Nevertheless, for Re = 100, the FOU and SOU results obtained for a 129×129 mesh agree well with published results for this mesh size [37]. Our results for Re = 400 on a 257×257 grid, with comparison to Ghia et al [37], Ben-Artzi et al [5] and De and Eswaran [6], are shown in Figures 11 and 12. It should also be noted that these author have used second-and fourth-order schemes for the convective terms.…”
Section: Lid-driven Cavity Flowsupporting
confidence: 93%
See 4 more Smart Citations
“…Nevertheless, for Re = 100, the FOU and SOU results obtained for a 129×129 mesh agree well with published results for this mesh size [37]. Our results for Re = 400 on a 257×257 grid, with comparison to Ghia et al [37], Ben-Artzi et al [5] and De and Eswaran [6], are shown in Figures 11 and 12. It should also be noted that these author have used second-and fourth-order schemes for the convective terms.…”
Section: Lid-driven Cavity Flowsupporting
confidence: 93%
“…Since Equations (6) and (7) are linear, u , v and p also satisfy Equation (6). These equations represent the dependence of the velocity corrections u and v on the pressure correction p .…”
Section: Pressure Correction Equationmentioning
confidence: 95%
See 3 more Smart Citations